2004
DOI: 10.1148/radiol.2302021465
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intracranial Aneurysms: Multi–Detector Row CT Angiography Compared with DSA

Abstract: Multi-detector row CT angiography has high sensitivity and specificity for detection of intracranial aneurysms, including small aneurysms, in patients with nontraumatic acute subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
97
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(105 citation statements)
references
References 11 publications
2
97
0
6
Order By: Relevance
“…Numerous studies that compare the diagnostic efficacy of multi-slice CTA with DSA have been published. The reported sensitivities of 4-slice CTA vary in the range of 81-100%, whereas the reported sensitivities of 16-and 64-slice CTA vary in the range of 92-100% (8,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The sensitivity of 92.8% found in the present study is consistent with the reported sensitivity values.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Numerous studies that compare the diagnostic efficacy of multi-slice CTA with DSA have been published. The reported sensitivities of 4-slice CTA vary in the range of 81-100%, whereas the reported sensitivities of 16-and 64-slice CTA vary in the range of 92-100% (8,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The sensitivity of 92.8% found in the present study is consistent with the reported sensitivity values.…”
Section: Discussionsupporting
confidence: 89%
“…Both of these cases occurred early in the study (the case with the 4 mm aneurysm located at RMCA was our first patient) when our experience was sub par. Lack of experience has been reported as a cause of misdiagnosis by other studies as well (2,8,18,24,32). Pedersen et al (32) reported an increase in the sensitivity of CTA from 88% to 94% after 1 year's experience.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It should also should depict aneurysms with a high degree of accuracy (11). Use of imaging for the evaluation of patients with an intracranial aneurysm involves detection and the origin origin of the aneurysm; demonstration of the sac, neck and the surrounding vascular anatomy; orientation of the sac according to the bony structures of the skull base; morphological features of the sac; presence or absence of intraluminal thrombus or peripheral calcifications and accurate measurements of the sac, neck and aneurysm filling (1).…”
Section: Discussionmentioning
confidence: 99%
“…7 However, as our experience with CTA has matured, we still see that there is a negative predictive value of only 82%-96%. 2,3 As such, patients with diffuse or sulcal SAH will still need DSA to exclude a causative vascular lesion.…”
mentioning
confidence: 95%